Characterization and regulation of microplastic pollution for protecting planetary and human health. (15th December 2022) - Jung, Youn Soo; Sampath, Vanitha; Prunicki, Mary; Aguilera, Juan; Allen, Harry; LaBeaud, Desiree; Veidis, Erika; Barry, Michele; Erny, Barbara; Patel, Lisa; Akdis, Cezmi; Akdis, Mubeccel; et al.
Abstract: Microplastics are plastic particles <5 mm in diameter. Since the 1950s, there has been an exponential increase in the production of plastics. As of 2015, it is estimated that approximately 6300 million metric tons of plastic waste had been generated of which 79% has accumulated in landfills or the natural environment. Further, it is estimated that if current trends continue, roughly 12, 000 million metric tons of plastic waste will accumulate by 2050. Plastics and microplastics are now found ubiquitously-in the air, water, and soil. Microplastics are small enough to enter the tissues of plants and animals and have been detected in human lungs, stools, placentas, and blood. Their presence in human tissues and the food chain is a cause for concern. While direct clinical evidence or epidemiological studies on the adverse effects of microplastic on human health are lacking, in vitro cellular and tissue studies and in vivo animal studies suggest potential adverse effects. With the ever-increasing presence of plastic waste in our environment, it is critical to understand their effects on our environment and on human health. The use of plastic additives, many of which have known toxic effects are also of concern. This review provides a brief overview of microplastics and the extent of the microplastic problem. There have been a few inroads in regulating plastics but currently these are insufficient to adequately mitigate plastic pollution. We also review recent advances in microplastic testing methodologies, which should support management and regulation of plastic wastes. Significant efforts to reduce, reuse, and recycle plastics are needed at the individual, community, national, and international levels to meet the challenge. In particular, significant reductions in plastic production must occur to curb the impacts of plastic on human and worldwide health, given the fact that plastic is not truly recyclable. Graphical abstract: Image 1 Highlights: Microplastics have been detected in plants, animals, and human tissues. In vitr o and animal studies suggest microplastics pose potential health risks. Microplastic pollution is expected to continue to increase rapidly. Research and policies to regulate plastics are urgently needed.